Advances in menopausal therapy: The tissue‐selective estrogen complex. Issue 3 (26th November 2012) - Moore, Anne
Abstract: Purpose: Most menopausal women experience vasomotor symptoms, vulvar‐vaginal atrophy, and/or bone loss. Although available estrogen and progestin therapies are effective in treating menopausal symptoms and preventing bone loss, some women may seek a therapy that provides symptom relief and has an improved tolerability profile. One option is a tissue‐selective estrogen complex (TSEC), or the pairing of estrogen(s) with a selective estrogen receptor modulator (SERM) to achieve the benefits of each component with fewer side effects. The first TSEC in clinical development combines the SERM bazedoxifene (BZA) with conjugated estrogens (CEs). The purpose of this article is to review published data for BZA/CE. Data sources: Data were obtained from phase 3 BZA/CE clinical trial study articles. Conclusions: Daily BZA 20 mg/CE 0.625 mg or 0.45 mg effectively relieved hot flushes, maintained or increased bone mineral density, treated vulvar‐vaginal atrophy, and improved quality of life. Further, BZA prevented stimulation of the endometrium by CE, and resulted in rates of amenorrhea and breast pain similar to placebo. Implications for practice: These results support the use of a TSEC consisting of BZA/CE as a promising therapy for managing the signs and symptoms from reduced estrogen levels associated with menopause.